Profile of the requests of hemocomponents hospital III Suárez Angamos 2015: Perfil de las solicitudes de hemocomponentes hospital III Suárez Angamos 2015 - Rivero Villegas, Kattia (2018)
ABSTRACT Introduction: To describe the profile in the applications of the blood components (PG, PFC, platelets), in Hospital III Suárez Angamos in the period January - December 2015. Methods: Observational, retrospective, cross-sectional, descriptive research carried out in the bank of Type I blood from Hospital III Suárez Angamos. The population is analyzed and presented according to age and sex group; followed by the population according to epidemiological variables. Results: 1,188 requests of blood hemocomponents, transfused 944 bags, 598 cases of patients, the field with the highest number of incomplete records is the main diagnosis, 371 records (62%); 389 (65%) women and 209 (35%) men were found, the older age group was the older adult (253 cases, 49%), with 522 (100%) requests for blood components and 471 (90%) ) transfusions; followed by the adult group (251 cases, 48%), with 484 (100%) requests and 331 (68%) transfusions. According to the type of care, 444 (74%) were complete, 60 (10%) of partial type and 90 (16%) received no attention. The emergency and gynecological services had the highest number of transfusion requests, 311 (52%) and 170 (28%), respectively, and the emergency internist had the highest number of attentions (287, 48%), the highest number of requests for globular packages (268 cases, 93%) and transfused 92% of the bags requested, followed by the gynecologist. We treated 563 (94%) cases with globular packages, 30 (5%) with fresh plasma and 5 (1%) with platelets; among the criteria used to standardize the main diagnostic field were 125 (55%) and laboratory 102 (45%); the most frequent diagnoses were anemia (91, 40%) and hemorrhage (76, 33%); the most frequent was severe anemia 62 (68%). Conclusion: Incomplete data in transfusion requests 62% (371 of 598 cases), the service with the highest percentage of patient cases, corresponds to emergency 52% followed by gynecology 28%, the type of hemocomponent most commonly used is the globular package 94%, especially in the emergency services (51% required, 287 of 563 cases) and gynecology (required 28%, 170 of 598 cases), the most frequent diagnosis found was anemia 40%, followed by hemorrhage 33%. Key words: Blood transfusion; Hemocomponent; Anemia. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1589